The Effect of Food and Beverage Attendant Service Quality on Guest Satisfaction at Stasionairy Restaurant, Union Station Hotel Nashville, United States - Aprianto Aprianto; Pasaribu Pasaribu (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2026)
The hospitality industry increasingly depends on service quality to satisfy guests and build loyalty. This study investigates the effect of Food and Beverage Attendant service quality on guest satisfaction at Stasionairy Restaurant in Union Station Hotel Nashville, United States. Motivated by negative guest reviews on Google Maps indicating dissatisfaction across key service dimensions, this quantitative study employed a simple linear regression approach. Using accidental sampling, data were collected from 97 guests who visited the restaurant in January 2026. The five SERVQUAL dimensions—tangibles, reliability, responsiveness, assurance, and empathy—were used to measure service quality (X), while guest satisfaction (Y) was measured through indicators including service meeting expectations, positive service memories, and willingness to revisit and recommend. Validity and reliability tests confirmed all instruments were sound. Results indicate that Food and Beverage Attendant service quality has a significant positive effect on guest satisfaction (p < 0.05), with service quality explaining a substantial portion of the variance in guest satisfaction. These findings affirm that improvements in service delivery by Food and Beverage Attendants—particularly in responsiveness and empathy—are critical to enhancing guest satisfaction and fostering loyalty in hotel restaurant settings.